Law question and answers: students companion : LLB solved papers / by Manish Arora and Santosh Kumar - Arora, Manish (New Delhi, 2012)
Law is more about learning the fundamentals than mere knowledge of different enactments. A student of law is faced with the niceties of law and is supposed to not only understand them but to score marks too, which is indeed a formidable combination. Of course, understanding legal principles is a matter of individual capability and scoring marks is about putting in labour with the right kind of books. But even if one has done a lot of labour one might not be able to score proportionate to his hard work because knowledge is one thing and presentation quite another. A lot of information wrapped and bundled would not fetch one any real marks but relatively less presented systematically can do wonders with the look of your marksheet. Answers have to be straight, to the point and crisp with brevity as an indispensable feature. And we, at UNIVERSAL, endeavour to assist you in doing just that.
Keywords: Law-Solved papers